Assessing the faecal source sensitivity and specificity of ruminant and human genetic microbial source tracking markers in the central Ethiopian highlands. (1st April 2021) - Linke, R.B.; Kebede, G.; Mushi, D.; Lakew, A.; Hayes, D.S.; Graf, W.; Farnleitner, A.H.
Abstract: This study tested genetic microbial source tracking (MST) methods for identifying ruminant‐ (BacR) and human‐associated (HF183/BacR287, BacHum) bacterial faecal contaminants in Ethiopia in a newly created regional faecal sample bank ( n = 173). BacR performed well, and its marker abundance was high (100% sensitivity (Sens), 95% specificity (Spec), median log10 8·1 marker equivalents (ME) g −1 ruminant faeces). Human‐associated markers tested were less abundant in individual human samples (median: log10 5·4 and 4·2 (ME + 1) g −1 ) and were not continuously detected (81% Sens, 91% Spec for BacHum; 77% Sens, 91% Spec for HF183/BacR287). Furthermore, the pig‐associated Pig2Bac assay was included and performed excellent (100% Sens, 100% Spec). To evaluate the presence of MST targets in the soil microbiome, representative soil samples were tested during a whole seasonal cycle ( n = 60). Only BacR could be detected, but was limited to the dry season and to sites of higher anthropogenic influence (log10 3·0 to 4·9 (ME + 1) g −1 soil). In conclusion, the large differences in marker abundances between target and non‐target faecal samples (median distances between distributions ≥log10 3 to ≥log10 7) and their absence in pristine soil indicate that all tested assays are suitable candidates for diverse MST applications in the Ethiopian area.